Detection of Maillard products of lactose in heated or processes milk by HPLC/DAD - Pischetsrieder, Monika; Groß, Ursula; Schoetter, Christiane (Zeitschrift für Lebensmittel-Untersuchung und -Forschung, 1999)
Two HPLC methods with diode array detection were used to separate Maillard products from milk components. The Maillard products 4-(β-D-galactopyranosyloxy)-2-hydroxy-2-methyl-2H-pyran-3(6H)-one (2), 1-[3-(/3-D-galactopyranosyloxy)-2-furanyl]-1-ethanohe (4), 4-(β-D-galactopyranosyloxy)-5-(hydroxymethyl)-2-methyl-3(2H)-furanone (5), isomaltol (7), maltol (9), 2,3-dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one (6), and 5-hydroxymethyl-2-furfuraldehyde (8) were determined using a water-methanol gradient. Furthermore, 4,5-dihydroxy-2-(β-D-galactopyranosyloxy)-5-methyl-2-cyclopenten-1-one (3) was separated from the milk components by applying the interaction reagent octylamine. Several heated or processed milk samples were analyzed, and formation of the Maillard products was determined and quantified. Thus it was found that 2 and 3 are early products of the Maillard reaction in milk, whereas after prolonged heating 4, 5, and particularly 9 and 6 become more important. Compounds 7 and 8 were not detected, even if the samples were heated under stringent conditions. © Springer-Verlag 1999.
UnivIS-Import:2015-03-05:Pub.1999.nat.dchph.llmch.detect
Keywords: Diode array detection; High performance liquid chromatography; Maillard reaction; Milk